2008
DOI: 10.1590/s0103-863x2008000100009
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem bioecológica e narrativas orais: um estudo com crianças vitimizadas

Abstract: Resumo: A partir de uma análise multifatorial do fenômeno da violência e respaldando-se em teorias que consideram a importância dos contos de fadas no desenvolvimento emocional infantil, realizou-se esta pesquisa com um grupo composto por três crianças vítimas de violência doméstica. Os objetivos do estudo foram: descrever o impacto das narrativas dos contos de fadas na emergência de conteúdos emocionais latentes, através das verbalizações das participantes durante as ações lúdicas, e traçar considerações a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
1
7
0
10
Order By: Relevance
“…Through verbal reports collected after the interventions with the stories, the researchers observed the emergence of participants' daily life contents, in addition to comments about confl icts which could put their development at risk. Based on the results, it was concluded that the interventions with stories revealed important information on participants' personal experiences, including the abuse experienced, which stresses the importance of such interventions in helping children atribute new meaning to their personal history (Alves & Emmel, 2008).…”
Section: Avaliação De Livros Infantis Brasileiros Sobre Prevenção De mentioning
confidence: 97%
See 1 more Smart Citation
“…Through verbal reports collected after the interventions with the stories, the researchers observed the emergence of participants' daily life contents, in addition to comments about confl icts which could put their development at risk. Based on the results, it was concluded that the interventions with stories revealed important information on participants' personal experiences, including the abuse experienced, which stresses the importance of such interventions in helping children atribute new meaning to their personal history (Alves & Emmel, 2008).…”
Section: Avaliação De Livros Infantis Brasileiros Sobre Prevenção De mentioning
confidence: 97%
“…What renders books with preventive plots so essential is the fact that they have the potential to help children who are experiencing problems, such as sexual abuse (Soma & Williams, 2014). Alves and Emmel (2008) conducted a study with three children and their caregivers referred to child protection services in São Paulo State, describing the impact on children and their mothers of fairy tales as emotional content facilitators. Through verbal reports collected after the interventions with the stories, the researchers observed the emergence of participants' daily life contents, in addition to comments about confl icts which could put their development at risk.…”
Section: Avaliação De Livros Infantis Brasileiros Sobre Prevenção De mentioning
confidence: 99%
“…De acordo com a teoria de Bronfenbrenner (2002), referencial utilizado durante o curso, os contextos de inserção em que os sujeitos estão inseridos, são compostos por quatro sistemas, sendo eles o microssistema, o mesossistema, exossistema e macrossistema. No mesossistema em consonância com as relações estabelecidas no microssistema, é estabelecida a rede de apoio social (ALVES, 2008).…”
Section: é Preciso Criar Uma Rede Entre Todas As Pessoas Que São Respunclassified
“…That theory has been used in several national studies (Dessen & Polonia, 2007;Alves & Emmel, 2008;Rolfsen & Martinez, 2008;Portes et al, 2013) about childhood problems in both health and education. The study by Custódio et al (2014) reported a critical review of the literature about social support networks in the context of preterm infants' development.…”
Section: Introductionmentioning
confidence: 99%